Effect of Canola oil on age-related changes in reproductive efficiency of Japanese quail males (Coturnix Coturnix japonica) - Razouki, Raad Hatem; Jalil, Mustafa Jawad; Haidar, Marwan Ibrahim; Razouki, Aqil Abdullah; Mohammed, Salman Daoud (Journal of agricultural, environmental and veterinary sciences, 2018)
This study conducted to evaluate the effect of canola oil on age – related changes in some reproductive efficiency indicators (testosterone،Histological traits of testis، sperm-egg penetration and malondialdehyde (MDA) in testis tissue) in Japanese quail males. A total of 75 Japanese quail males (19 weeks old) were distributed into 5 groups (0، 0.25، 0.5، 0.75 and 1.0 ml/kg diet) as T1، T2، T3، T4 and T5 respectively. The study lasted 8 weeks (from 20 to 28 weeks of age). Results revealed that adding canola oil to the diet (T2, T3, T4 and T5) resulted in significant (p≤ 0.05) and (p≤ 0.01) increase in testosterone and sperm- egg penetration at 24 and 28 weeks respectively and significant (p≤0.01) decrease in MDA construction in testis tissue. Also, there were a significant (p≤0.05) increase in absolute and relative weights of testis and significant (p≤ 0.01) increase in seminiferous tables and germinal cells thickness and there was significant improvement in volume density and relative weight of seminiferous tubules and interstitial tissue components compared with control group (T1). On other hand, the best results were achieved in T5 compared to other canola oil groups. Therefore, adding canola oil to the diet could be used as an efficient tool for limit the negative effects in reproductive efficiency of Japanese quail males as result of age.